A Bibliometric Analysis of Nanocrystalline Cellulose Research as Medical Implant Using VOSviewer - Deaniar Hafilah; Asep Bayu Dani Nandiyanto (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2022)
Background: Nanocrystalline cellulose has potential for biomedical applications due to its abundant material availability, biodegradability, biocompatibility, and low weight. Research on nanocrystalline cellulose as medical implants has rarely been studied in the past 10 years, although this material has tremendous potential such as bone implants and cardiovascular implants. Objective: This study aims to analyze the development of research on nanocrystalline cellulose as medical implants using a bibliometric approach with computational analysis using VOSviewer. Methods: The article data was obtained using the Publish or Perish software by retrieving the database from Google Scholar. The keyword “nanocrystalline cellulose, medical implants, biomedical